Qualitative Forschung mit lebenslimitierend erkrankten Kindern und Jugendlichen: Hören wir richtig hin? = Conducting qualitative research on children and adolescents with life-limiting conditions : are we really listening? - Oetting-Roß, Claudia; Ullrich, Charlotte; Schnepp, Wilfried; Büscher, Andreas (Forum qualitative Sozialforschung, 2016)
DOAJ is an online directory that indexes and provides access to quality open access, peer-reviewed journals.
Gesehen am 15.10.2019